Lumen : the art and science of light, 800-1600 - Arslan, Taha Yasin (J. Paul Getty Museum, 2024)
"This publication is issued on the occasion of the exhibition Lumen: The Art and Science of Light, 800-1600, on view at the J. Paul Getty Museum at the Getty Center, Los Angeles, from September 10 to December 8, 2024. The catalogue examines how medieval Christian, Jewish, and Islamic artists, theologians, and thinkers studied light and its properties to better perceive and understand the sacred"--